Kemampuan Literasi Numerasi dalam Pembelajaran Tematik Siswa Kelas IV SD Negeri 1505 Pasir Julu - Astria Silvera Harahap, Rani (Proceeding of Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2023)
Numeracy literacy is one of the important literacy that students must master. By having good numeracy literacy skills, students are able to competently apply their mathematical knowledge in real life. The purpose of this study is to describe numeracy literacy skills in thematic learning in grade IV students of Public Elementary School 1505 Pasir Julu. The method used in this study is descriptive qualitative. The data collection uses interview techniques with grade IV teachers at Public Elementary School 1505 Pasir Julu, tests and documentation. The results of this study show that the numeracy literacy skills of grade IV students of Public Elementary School 1505 Pasir Julu are already in the category of quite good. This can be seen from the students’ understanding to understand the logic of the story is good enough, In addition, students have been able to answer well and correctly about numeracy literacy. However, the results obtained still need to be improved again.